Fibre optic interconnecting devices and passive components performance standard. Non-connectorised single-mode bidirectional 1490 / 1550 nm downstream 1310 nm upstream WWDM devices for category C. Controlled environment Part 086-2, (31st January 2010) - British Standards Institution,
No abstract available